An example of the utility of genomic analysis for fast and accurate clinical diagnosis of complex rare phenotypes. Issue 1 (December 2017) - Le Quesne Stabej, Polona; James, Chela; Ocaka, Louise; Tekman, Mehmet; Grunewald, Stephanie; Clement, Emma; Stanescu, Horia; Kleta, Robert; Morrogh, Deborah; Calder, Alistair; Williams, Hywel; Bitner-Glindzicz, Maria
Abstract Background We describe molecular diagnosis in a complex consanguineous family: four offspring presented with combinations of three distinctive phenotypes; non-syndromic hearing loss (NSHL), an unusual skeletal phenotype comprising multiple fractures, cranial abnormalities and diaphyseal expansion, and significant developmental delay with microcephaly. We performed Chromosomal Microarray Analysis on the offspring with either the skeletal or developmental delay phenotypes, and linkage analysis and whole exome sequencing (WES) on all four children, parents and maternal aunt. Results Chromosomal microarray and FISH analysis identified ade novo unbalanced translocation as a cause of the microcephaly and severe developmental delay. WES identified a NSHL-causing splice variant in an autosomal recessive deafness genePDZD7 which resided in a linkage region and affected three of the children. In the two children diagnosed with an unusual skeletal phenotype, WES eventually disclosed a heterozygousCOL1A1 variant which affects C-propetide cleavage site ofCOL1 . The variant was inherited from an apparently unaffected mosaic father in an autosomal dominant fashion. After the discovery of theCOL1A1 variant, the skeletal phenotype was diagnosed as a high bone mass form of osteogenesis imperfecta. Conclusions Next generation sequencing offers an unbiased approach to molecular genetic diagnosis in highly heterogeneous and poorly characterised disorders and enables early diagnosis as well as detection of mosaicism.